2017
DOI: 10.1080/19420862.2017.1409319
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of tumor by CD47/PD-L1 dual-targeting fusion protein that engages innate and adaptive immune responses

Abstract: The host immune system generally serves as a barrier against tumor formation. Programmed death-ligand 1 (PD-L1) is a critical "don't find me" signal to the adaptive immune system, whereas CD47 transmits an anti-phagocytic signal, known as the "don't eat me" signal, to the innate immune system. These and similar immune checkpoints are often overexpressed on human tumors. Thus, dual targeting both innate and adaptive immune checkpoints would likely maximize anti-tumor therapeutic effect and elicit more durable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 49 publications
(65 reference statements)
2
58
0
Order By: Relevance
“…Therefore, combinations with T-cell checkpoint inhibitors (with anti-PD-1 or PD-L1 agents) may further augment T cell responses and enhance efficacy. Several pre-clinical studies have demonstrated that CD47 blockade in combination with T cell checkpoint inhibitors can enhance antitumor activity (37)(38)(39). A clinical trial evaluating magrolimab in combination with atezolizumab (an anti-PD-L1 antibody) has been initiated in R/R AML (NCT03922477).…”
Section: Novel Combinations With Cd47 Targeting Agents and Future Dirmentioning
confidence: 99%
“…Therefore, combinations with T-cell checkpoint inhibitors (with anti-PD-1 or PD-L1 agents) may further augment T cell responses and enhance efficacy. Several pre-clinical studies have demonstrated that CD47 blockade in combination with T cell checkpoint inhibitors can enhance antitumor activity (37)(38)(39). A clinical trial evaluating magrolimab in combination with atezolizumab (an anti-PD-L1 antibody) has been initiated in R/R AML (NCT03922477).…”
Section: Novel Combinations With Cd47 Targeting Agents and Future Dirmentioning
confidence: 99%
“…Boussiotis extensively reviewed the PD-1/PD-L1 axis and its potential role in cancer therapy [74]. Previous studies showed enhanced anti-tumor effect with dual targeting of both CD47 and PD-L1 in melanoma and colon carcinoma [75,76]. Lian and colleagues designed an Ep-CAM (epithelial cell adhesion molecule) liposome containing both CD47 and PD-L1 arms.…”
Section: Dual Blockade Of Cd47 and Pd-l1mentioning
confidence: 99%
“…Anti-SIRPα antagonists have also been combined with tumor-opsonizing antibodies such as rituximab showed anti-tumor efficacy in vitro [ 82 ] and in xenograft lymphoma and colon cancer models [ 86 ]. Similarly, targeting CD47 and PD-L1 [ 75 , 76 ].…”
Section: Insights and Challenges In Targeting Cd47 In Hematological Mmentioning
confidence: 99%
“…This therapeutic activity required simultaneous binding to CD20 and CD47 and was not detected in single CD47-positive cells [ 195 ]. Several other IgG-based CD47-targeting bispecific antibodies have been developed, among others CD20-CD47 [ 196 ] and CD70-KWAR23 [ 166 ] CD47-CD19 [ 197 , 198 ], CD47-MSLN [ 197 ], CD47-PDL1 [ 199 , 200 ], and PD-L1-SIRPα [ 201 ]. However, the impact of these bispecific antibodies on neutrophil-mediated phagocytosis and trogocytosis has not been delineated yet.…”
Section: Fcr-mediated Neutrophil Activation; Targeting Fcγriia (Cdmentioning
confidence: 99%